Dose Response of Endotoxin on Hepatocyte and Muscle Mitochondrial Respiration In Vitro. (12th January 2015) - Jeger, Victor; Brandt, Sebastian; Porta, Francesca; Jakob, Stephan M.; Takala, Jukka; Djafarzadeh, Siamak
Abstract : Introduction. Results on mitochondrial dysfunction in sepsis are controversial. We aimed to assess effects of LPS at wide dose and time ranges on hepatocytes and isolated skeletal muscle mitochondria. Methods. Human hepatocellular carcinoma cells (HepG2) were exposed to placebo or LPS (0.1, 1, and 10 μ g/mL) for 4, 8, 16, and 24 hours and primary human hepatocytes to 1 μ g/mL LPS or placebo (4, 8, and 16 hours). Mitochondria from porcine skeletal muscle samples were exposed to increasing doses of LPS (0.1–100 μ g/mg) for 2 and 4 hours. Respiration rates of intact and permeabilized cells and isolated mitochondria were measured by high-resolution respirometry. Results. In HepG2 cells, LPS reduced mitochondrial membrane potential and cellular ATP content but did not modify basal respiration. Stimulated complex II respiration was reduced time-dependently using 1 μ g/mL LPS. In primary human hepatocytes, stimulated mitochondrial complex II respiration was reduced time-dependently using 1 μ g/mL LPS. In isolated porcine skeletal muscle mitochondria, stimulated respiration decreased at high doses (50 and 100 μ g/mL LPS). Conclusion. LPS reduced cellular ATP content of HepG2 cells, most likely as a result of the induced decrease in membrane potential. LPS decreased cellular and isolated mitochondrial respiration in a time-dependent, dose-dependent and complex-dependent manner.